2019
DOI: 10.1002/jcla.23057
|View full text |Cite
|
Sign up to set email alerts
|

Effect factors related to a high probability of hemodialysis independence in newly diagnosed multiple myeloma patients requiring hemodialysis

Abstract: Background Renal failure is a severe complication of symptomatic myeloma, related to higher mortality. Recovery from dialysis dependence can lead to enormous survival benefits. We investigated the effect factors for probability of dialysis independence. Methods Retrospective data on 45 newly diagnosed MM (NDMM) patients with serious renal impairment and requiring hemodialysis were analyzed. The statistical methods including logistic regression analysis, Kaplan‐Meier survival curves, the log‐rank test and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…In addition, miRNAs were negatively correlated with LDH (P < .05) in MM. These serum parameters reflecting the tumor load of MM, not only relate to the clinical stage, but also affect the renal function and prognosis of MM patients [27][28][29]. In our previous study, we demonstrated that these serum indicators were related to MM prognosis 30.…”
mentioning
confidence: 87%
“…In addition, miRNAs were negatively correlated with LDH (P < .05) in MM. These serum parameters reflecting the tumor load of MM, not only relate to the clinical stage, but also affect the renal function and prognosis of MM patients [27][28][29]. In our previous study, we demonstrated that these serum indicators were related to MM prognosis 30.…”
mentioning
confidence: 87%
“…Substantial FLCs (nephrotoxic proteins) accumulated in the proximal tubular epithelium are responsible for most tubulointerstitial injuries. Monoclonal light chains in renal tubules stimulate the production of some proinflammatory cytokines, including macrophage chemoattractant protein-1 (MCP-1), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α), which subsequently, rapidly leads to renal tubulointerstitial fibrosis [11,12]. Light chain proteins can also cause glomerular function impairment when deposited on the glomerular basement membrane (GBM) and mesangial area [13].…”
Section: The Relationship Between Cystatin C and Myeloma Nephropathymentioning
confidence: 99%